2013
DOI: 10.3126/nepjoph.v5i1.7816
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tear secretion and tear film instability in cases with pterygium and normal subjects

Abstract: Introduction: Dry eye is a common disorder affecting a significant percentage of the population. Materials and methods: This study is a prospective, hospital-based, case-controlled study conducted between January 2009 and May 2010. Seventy-six pterygium cases and 152 age-and-sex matched controls presenting to the OPD of Manipal Teaching Hospital were included. The TBUT Schirmer's test and basal tear secretion were estimated in all patients. A TBUT of less than 10 seconds and a Schirmer's test of less than 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…Roka N et al also found that redness was the most common symptom of pterygium patients followed by grittiness and burning sensation. 4 Ganeshpuri AS et al also found that burning sensation, grittiness and redness were the common symptoms of pterygium patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Roka N et al also found that redness was the most common symptom of pterygium patients followed by grittiness and burning sensation. 4 Ganeshpuri AS et al also found that burning sensation, grittiness and redness were the common symptoms of pterygium patients.…”
Section: Discussionmentioning
confidence: 96%
“…4 Ganeshpuri AS et al in India had found strong relationship between dry eye, diabetes and pterygium.…”
Section: Clinical Correlation Of Dry Eye and Pterygiummentioning
confidence: 96%
See 2 more Smart Citations
“…17,18 Daha önceki çalışmalarda kuru göz ve inflamasyon arasındaki ve kuru göz ve pterjium arasındaki pozitif ilişki gösterilmiştir. 19,20 Bu nedenle bizim çalışmamızda inflamasyonu ve oküler yüzey hasarını azaltması ve inflamatuvar yıkım ürünlerini oküler yüzeyden uzaklaştırması açısından siklosporin A'ya ilave olarak hidroksipropilmetilselüloz suni gözyaşı 4x1 eklenilmiştir. Siklosporin A+hidroksipropilmetilselüloz kullanan gruplardan grup 2'de hiç nüks görülmezken grup 1'de bir olguda nüks geliştiği görülmüştür.…”
Section: Discussionunclassified